Covid-19, Waste Production and Municipal Recycling Programs: Insights from Chile to the Global South - Vasquez-Perez, O; Espinoza-Perez, A; Rojo-Gonzalez, L; Davila-Galvez, S (Elsevier B.V., 2023)
The amount and characterization of municipal and industrial waste generated in numerous cities worldwide have changed dramatically in recent years due to the COVID-19 pandemic. Consequently, assessing the impact of COVID-19-related policies is important to provide decision-makers with adequate knowledge to respond effectively to future events and create successful policies that respond to specific contexts. This study focuses on Chile, Latin America s second-largest municipal and industrial solid waste producer, with tight quarantine procedures placed to prevent the virus from spreading, and a series of monetary incentives implemented to minimize the economic and social impact of the quarantines. The time series of municipal solid waste (MSW) and recycling in the metropolitan region show a decrease in the amount collected during the initial months of lockdown and a subsequent increase during monetary incentive implementation. The country recovered and exceeded pre-pandemic MSW generation and recycling levels. Furthermore, the lockdown and the withdrawal of retirement funds (WRF) had a varied impact on each municipality in the region. However, WRF had a larger direct impact than a lockdown, indicating that purchasing power has a greater impact than mobility in waste generation and recycling, at least in this region of Chile. © 2023 Elsevier B.V.
Keywords: Municipal solid waste management; COVID-19; Recycling; Developing countries; Time series analysis; Monetary incentives